Pengembangan Modul Digital IPA Berbasis Kearifan Lokal Aceh untuk Melatih Kemampuan Critical Thinking Siswa di Era Society 5.0 - Khairunnisak Khairunnisak; Khairuni Khairuni (Departement of Mathematics Education, 2024)
This study aims to develop a digital science module centered on the theme of Waves and Sound, integrating aspects of Acehnese local wisdom. The module is designed to enhance students' critical thinking skills within the Society 5.0 framework. To support this goal, the module incorporates elements of Acehnese culture, such as traditional musical instruments and folklore linked to natural phenomena, making it easier for students to grasp the core concepts of waves and sound. The study employed a quasi-experimental design along with research and development (R&D) methodology. Pre-tests and post-tests were conducted to measure the improvement in critical thinking skills between the experimental and control groups. Findings indicated that the local wisdom-based digital module effectively reinforced students' understanding of waves and sound and significantly developed their critical thinking abilities.